Leather specification according IULTCS part II, Continuation and discussion - Soebijarso, Koentoro (Majalah Kulit, Karet, dan Plastik, 1995)
This Part II publication of Leather Specification According IULTSC (the International Union of Leather Technologists and Chemists Societies), is the continuation of Part I edition, in the bulletin âSain dan Teknologi Kulitâ ISSN : 0853-3660, no.2 th.II, Desember 1991. In this publication the writer will concentrate on the specification of shoe uppers, lining and upholstery leather. At the end of this publication a discussion on IULTCS specification and IUF, IUP, IUC, etc. test methods for the benefit of the Government, tanners and scientists will be conducted. This is to consider the existing Indonesian Industrial Standard that already adopted as Indonesian Nasional Standard.Â